Switching among branded and generic medication products during ongoing treatment of psychiatric illness. Issue 1 (10th January 2020) - Habert, Jeffrey; Margolese, Howard C; Wilson, Adriana; Boucher, Matthieu; Blier, Pierre
Abstract : Switches between branded (reference) medications and the corresponding generic medications or between two different corresponding generic medications occur commonly during the treatment of central nervous system disorders. Prescribing a generic product in place of a reference product can reduce patient and pharmacy costs. But there can be implications. Planned or unplanned switches from one product to another during ongoing treatment may introduce variability in drug exposure which could in turn compromise efficacy and/or tolerability. Studies comparing the initiation of reference versus generic products do not provide clear evidence of the superiority of reference or generic products generally, whereas several studies examining a switch between reference and generic products suggest that reductions in efficacy or medication adherence and persistence may be associated with generic substitution. Clinicians should work with patients to facilitate a consistent supply of reference or generic drug product that provides stable exposure to avoid clinical deterioration or poor tolerability.